Embodying Popular Piety: Code of Conduct and Death Anniversary in the Ṭarīqah Qādiriyyah wa Naqshbandiyyah - Asfa Widiyanto (Ulumuna, 2016)
This paper investigates how the code of conducts and devotion to the leaders develop in the Sufi orders, and how these shape the notion of “popular piety”, by paying a particular attention to the Ṭarīqah Qādiriyyah Wa Naqshbandiyyah (TQN) in Mranggen, Central Java. This article starts with highlighting the ways in which the leaders of the TQN prescribe a set of rules of conduct, and how this set of rules is grounded on “web of beliefs and practices” of the community in question. It also delves into the ways in which the followers acknowledge this code of conduct, on the one hand, and respect their living and death leaders, on the other hand. It argues that code of conduct and leaders’ death anniversary contribute to the moulding of popular piety within the Muslim community, in general, and among members of the TQN in particular. DOI: http://dx.doi.org/10.20414/ujis.v20i2.979